The gastro-esophageal reflux disease questionnaire using Indonesian language: A language validation survey (Medical Journal of Indonesia, 2011)
Background: The aims of this study were to test the usefulness of the Gastro-esophageal Reflux Disease Questionnaire (GERDQ) in the diagnosis of GERD, to validate the GERDQ written in Indonesian language, and to evaluate the reliability of the GERDQ for use in Indonesian-speaking GERD patients (Virginia study). Methods: This was a prospective survey of 40 patients diagnosed with GERD, based on an endoscopic examination, in 3 cities in Indonesia (Jakarta, Bandung, and Surabaya) from 15 January to 15 May 2009. Patients were asked to complete the GERDQ, and the validity and reliability of the questionnaire were assessed. Results: The percentages of respondents who reported symptoms lasting 4-7 days were as follows: 68% had a burning sensation behind the breastbone (heartburn); 65% had stomach content (fluid) move upwards to the throat or mouth (regurgitation); 70% had a pain in the centre of the upper abdomen; 58% had nausea; 63% had difficulty sleeping because of the heartburn and/or regurgitation; and 63% took additional medication for heartburn and/or regurgitation. Cronbach's alpha was 0.83, indicating that all of the questions in the Indonesian-language GERDQ are valid and reliableÂ for Indonesian GERD patients. Conclusions: This study achieved the primary objectives and showed that the GERDQ is valid and reliable for use with Indonesian-speaking GERD patients. The results were consistent with those of the DIAMOND study, which showed that the GERDQ can be used to diagnose GERD on the basis of the reported symptoms. (Med J Indones 2011; 20:125-30)